The Effect of Jakaba on the Growth and Pest Resistance of Borokoli (Brassica oleracea L) - Husni, Rafeah (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to see the effect of Jakaba liquid organic fertilizer in increasing the growth and resistance of broccoli plants ( Brassica oleracea L. ) to leaf pest attacks. The study used an experimental design with three treatment groups, namely the group given Jakaba fertilizer, the group given NPK fertilizer, and the control group (without fertilizer). The study was conducted in Hutarimbaru Village from March to May 2025. The parameters observed included plant height, number of leaves, flower formation, and intensity of leaf pest attacks. The data obtained were analyzed using descriptive statistical analysis and ANOVA to determine significant differences between treatments. The results showed that Jakaba fertilizer increased the growth of broccoli plants and improved resistance to leaf pest attacks better than the control. NPK fertilizer also showed a significant increase in growth, but was not better in terms of pest resistance compared to Jakaba. This study concludes that Jakaba fertilizer can be an alternative environmentally friendly fertilizer in sustainable broccoli cultivation.